The effectiveness of anaerob-aerob biofilter and phytoremediation using Salvinia molesta for reducing phosphateand MBAS (Methylen Blue Active Substance)content in laundry liquid waste - Eko Saputra; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The laundry waste is rich in MBAS and phosphate and its need to be processed before being flown to environment. This study aimsto determine the ability of abatchbiofilter system in reducingthe phosphate and MBAS content. This study has been conducted in January-March 2018.The laundry liquid waste (175 liters) was kept in 2 anaerobik tanks that was completed with gravel, sand and palm fibers media for ten days.Then the waste was flown to aerobik tanks (coconut shellcharcoal media) for seven days. Finallythe wastewas treated in a phytoremediation pondthat was completed withSalvinia molestafor fifteen days. By the end of the experiment, the phosphate reduced from 11.6-0.8 mg/L (the effectiveness was 92.67%)and the MBAS reduced from 10.5-1.3 mg/L (the effectiveness was 87.16%). Other water quality parameters such as pH was normal and temperature and DO were improved. The treated waste was then used for rearing Cyprinus carpio (5-7 cm TL) for 10 days. The survival rate of the fish was 89%. Based on data obtained, it can be concluded that the combination of biofiters and phytoremediation system using Salvinia molesta is effective to reduce the phosphate and MBAS content in the laundry liquid waste. Keyword:waste water, detergent contaminated waste, bacth system, surfactant